Increasing variance in North Pacific climate relates to unprecedented ecosystem variability off California. (25th March 2013) - Sydeman, William J.; Santora, Jarrod A.; Thompson, Sarah Ann; Marinovic, Baldo; Lorenzo, Emanuele Di
Abstract Changes in variance are infrequently examined in climate change ecology. We tested the hypothesis that recent high variability in demographic attributes of salmon and seabirds off California is related to increasing variability in remote, large‐scale forcing in the North Pacific operating through changes in local food webs. Linear, indirect numerical responses between krill (primarily Thysanoessa spinifera) and juvenile rockfish abundance (catch per unit effort (CPUE)) explained >80% of the recent variability in the demography of these pelagic predators. We found no relationships between krill and regional upwelling, though a strong connection to the North Pacific Gyre Oscillation (NPGO) index was established. Variance in NPGO and related central Pacific warming index increased after 1985, whereas variance in the canonical ENSO and Pacific Decadal Oscillation did not change. Anthropogenic global warming or natural climate variability may explain recent intensification of the NPGO and its increasing ecological significance. Assessing non‐stationarity in atmospheric‐environmental interactions and placing greater emphasis on documenting changes in variance of bio‐physical systems will enable insight into complex climate‐marine ecosystem dynamics.